2017
DOI: 10.1108/wje-08-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Bio-oil production from fast pyrolysis of maple fruit (acer platanoides samaras): product yields

Abstract: Purpose The purpose of this paper is to investigate fast pyrolysis of maple fruit as an energy sources. This could serve as a solution to the energy sources problem. Design/methodology/approach Fast pyrolysis of maple fruit (samara) was achieved in a fixed bed reactor. The pyrolysis experiments have been conducted on the sample of maple seeds to particularly determine the effects of pyrolysis temperature, particle size and sweep gas flow rate on the pyrolysis product yields. Findings The oil of maple fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The heating value of a raw material mixture of tea bush, walnut shell, and pine cone in equal quantities and subjected to fast pyrolysis is 17.67 MJ kg −1 . The heating value of the raw bio-oil generated by fast pyrolysis is determined to be 24.66 MJ kg −1 under the most efficient circumstances (50 cm 3 .min −1 nitrogen flow rate, 100 • C.min −1 heating rate, and 500 • C pyrolysis temperature).…”
Section: Proximate Analysis Results Applied To the Biomass Sample Mix...mentioning
confidence: 99%
See 3 more Smart Citations
“…The heating value of a raw material mixture of tea bush, walnut shell, and pine cone in equal quantities and subjected to fast pyrolysis is 17.67 MJ kg −1 . The heating value of the raw bio-oil generated by fast pyrolysis is determined to be 24.66 MJ kg −1 under the most efficient circumstances (50 cm 3 .min −1 nitrogen flow rate, 100 • C.min −1 heating rate, and 500 • C pyrolysis temperature).…”
Section: Proximate Analysis Results Applied To the Biomass Sample Mix...mentioning
confidence: 99%
“…Using the graphic data in Figures 11-15, the impacts of pyrolysis conversion, liquid efficiency, solid efficiency, and gas efficiency are assessed. The highest value in Figure 11 is 57.9 wt% at 300 cm 3 .min −1 , while the lowest is 47.84 wt% at 50 cm 3 .min −1 at 300 °C and 100 °C.min −1 . It has been found that the nitrogen flow rate has less impact on pyrolysis conversion at middle speeds (100-200 cm 3 .min −1 ).…”
Section: Nitrogen Flow Rate Influence On Pyrolysis Product Yieldsmentioning
confidence: 91%
See 2 more Smart Citations
“…Οι τιμζσ των αποδόςεων για ενδιάμεςεσ κερμοκραςίεσ (600 °C) βρίςκονται ανάμεςα ςτισ δφο παραπάνω τιμζσ. Θ μζγιςτθ, για το βιοζλαιο, απόδοςθ εντοπίηεται ςε κερμοκραςία πυρόλυςθσ τουσ 600 °C και πιο ςυγκεκριμζνα ςε τιμι 47,7 wt%, μία τιμι παρόμοια(Bahadir, Kar, Keles, & Kaygusuz, 2017;Sutrisno & Hidayat, 2018) και ςε κάποιεσ περιπτϊςεισ υψθλότερθ(Önal, Uzun, & Pütün, 2017) ςε ςφγκριςθ με τισ αντίςτοιχεσ αποδόςεισ βιοελαίων που λαμβάνονται από πυρόλυςθ παρεμωερϊν υλικϊν από υπολείμματα του τομζα τθσ βιομθχανίασ τροωίμων. Αυτό αποκαλφπτει ότι θ παραπάνω κερμοκραςία κα πρζπει να κεωρείται ωσ θ βζλτιςτθ για τθ παραλαβι μεγαλφτερων ποςοτιτων του ςυγκεκριμζνου προϊόντοσ τθσ πυρόλυςθσ.…”
unclassified